Effectiveness of Triamcinolone and Lidocaine in Patient with Piriformis Syndrome – A Case Series - Setianti, Ariani Rahayu; Hidayati, Hanik Badriyah (Brawijaya University, 2019)
Piriformis syndrome (PS) has been documented as a contributory cause for sciatica, buttock, and low back pain. The worldwide incidence of PS would be about 2,4 million per year. The management of piriformis syndrome includes injection of the piriformis muscle with local anesthetic and steroid, however, the study for the effectiveness of the combination is lacking especially in Indonesian population. This case illustrates the effectiveness reduction of triamcinolone in combination with lidocaine measured by Visual Analogue Scale (VAS) in patient suffered from PS.Â